Teaching and learning processes in Professional and Technological Education: reflections about theory and its implementation (Research, Society and Development, 2021)
The work presented aims to provide reflections on the conceptual bases of professional and technological education (EPT), discussing some of its structuring pillars - omnilaterality, full development of human potential and integral human formation - and their approximations and/or distances in relation to the different approaches to the teaching and learning process, focusing on the sociocultural approach. The methodology used consists of bibliographical research, having as main references articles and books. As for the results and discussions, it is observed the approach of EPT with the sociocultural theory and its distancing from traditional and behavioral teaching theories and approaches, distances in relation to relationship between teacher and student, with the humanist and cognitive approaches. As a conclusion of the study, the necessary attention to the theoretical foundations of the EPT and the necessary dialogue that must be permanently established with the teaching and learning approaches, in order to become the guiding praxis of the teaching action, which requires the continued training of teachers. The teaching praxis based on these assumptions effectively contributes to quality education, which is reflective, critical and imbricated with social reality.